Química de materiais em 25 anos de SBQ - Rubira, Adley Forti; Zarbin, Aldo José Gorgatti; Galembeck, Fernando; Alves, Oswaldo Luiz; Jafelicci Júnior, Miguel [UNESP] (Sociedade Brasileira de Química, 2002)
Communications on Chemistry of Materials topics were already presented in the first annual meetings of the Brazilian Chemical Society, dispersed throughout various meeting sections. The SBQ Materials Chemistry division was organized in 1993, attracting those members with an interest in the composition, structure and properties of materials, as related to their functions. This paper is an account of the development of Materials Chemistry research in Brazil, based on the SBQ annual meetings data.
Materials chemistry in 25 years of Brazilian chemical society
Keywords: Chemistry; Brazilian Chemical Society; SBQ; Materials Chemistry